2018
DOI: 10.5455/njppp.2018.8.1248725122017
|View full text |Cite
|
Sign up to set email alerts
|

Pain sensitivity and cardiovascular reactivity to the experimental induced cold pressor pain during different phases of menstrual cycle in young Indian females

Abstract: Background: Many previous research studies have shown a higher prevalence of chronic pain conditions as well as more pain sensitivity or lesser pain thresholds (PTh) among women as compared to men. It might be related to the effect of female reproductive hormones, as these hormones produce its effect on various aspects of physiological systems. Aims and Objectives: The aim of this study is to find the differences in the pain responses as well as cardiovascular reactivity during cold pressor test in different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…However, the authors noted that the more well-controlled studies mostly did not find any effect of the menstrual cycle phase on pain sensitivity, although these studies were not without some of the methodological limitations as pointed out by Sherman and LeResche (2006) . To the best of our knowledge, nine recent studies have been published since the time of the last review in 2015 ( Bartley et al, 2015 ; Iacovides et al, 2015b ; Cankar et al, 2016 ; Palit et al, 2016 ; Alves et al, 2017 ; Nayak et al, 2017 ; Jasrotia et al, 2018 ; Payne et al, 2019 ; Pogatzki-Zahn et al, 2019 ); these findings also appear to be inconsistent. There is a roughly equal number of studies that observed variations in pain sensitivity across the menstrual cycle (5/9 studies) and those that did not (4/9 studies).…”
Section: Pain In Womenmentioning
confidence: 99%
“…However, the authors noted that the more well-controlled studies mostly did not find any effect of the menstrual cycle phase on pain sensitivity, although these studies were not without some of the methodological limitations as pointed out by Sherman and LeResche (2006) . To the best of our knowledge, nine recent studies have been published since the time of the last review in 2015 ( Bartley et al, 2015 ; Iacovides et al, 2015b ; Cankar et al, 2016 ; Palit et al, 2016 ; Alves et al, 2017 ; Nayak et al, 2017 ; Jasrotia et al, 2018 ; Payne et al, 2019 ; Pogatzki-Zahn et al, 2019 ); these findings also appear to be inconsistent. There is a roughly equal number of studies that observed variations in pain sensitivity across the menstrual cycle (5/9 studies) and those that did not (4/9 studies).…”
Section: Pain In Womenmentioning
confidence: 99%